What have gonadotrophin overexpressing transgenic mice taught us about gonadal function? - Rulli, Susana Beatriz (2005)
The two gonadotrophins, follicle-stimulating hormone and luteinising hormone, are pivotal regulators of the development and maintenance of normal fertility by maintaining testicular and ovarian endocrine function and gametogenesis. Too low gonadotrophin secretion, i.e. hypogonadotrophic hypogonadism, is a common cause of infertility. But there are also physiological and pathophysiological conditions where gonadotrophin secretion and/or action are either transiently or chronically elevated, such as pregnancy, pituitary tumours, polycystic ovarian syndrome, activating gonadotrophin receptor mutations, perimenopause and menopause. These situations can be either the primary or secondary cause of infertility and gonadal pathologies in both sexes. Also the role of gonadotrophins as tumour promoters is possible. Recently, the possibility to combine information from genetically modified mice and human phenotypes in connection with mutations of gonadotrophin or gonadotrophin receptor genes has elucidated many less well known mechanisms involved in dysregulation of gonadotrophin function. Among the genetically modified mouse models, transgenic mice with gonadotrophin hypersecretion have been developed during the last few years. In this review, we describe the key findings on transgenic mouse models overexpressing gonadotrophins and present their possible implications in related human pathologies. In addition, we provide examples of genetic mouse models with secondary effects on gonadotrophin production and, consequently, on gonadal function.